Mortality Trends of Air Pollution-Sensitive Diseases in Jakarta, Indonesia: A Population-Based Analysis, 2019-2023 - Fauzia, Sifa; Zakianis; Susilowati, Indri Hapsari; Maulida, Rizka (International Journal of Science and Society, 2025)
Air pollution is a leading environmental health risk, especially in megacities with limited monitoring infrastructure. In Jakarta, few studies have examined mortality trends for air pollution-sensitive diseases. This population-based study analyzed registered deaths in Jakarta (2019–2023) attributed to cardiovascular and respiratory diseases linked to air pollution. Mortality data were disaggregated by disease type, age, sex, region, and reporting facility. Stroke consistently accounted for the highest number of deaths, increasing by 36% from 2020 to 2023. Pneumonia and influenza declined until 2022 but surged in 2023 by 48%. Senior adults (≥60 years) bore the highest burden, and men consistently had higher death counts than women. East Jakarta recorded the highest regional mortality, while Thousand Islands had the lowest. Reporting by community health centers grew steadily, reaching 48.3% of all reported deaths in 2023. Mortality trends in Jakarta reflect a growing burden of air pollution-sensitive diseases, particularly among the elderly and in more polluted districts. Expanding surveillance coverage, improving cause-of-death certification, and integrating mortality with environmental data are essential for guiding air quality and health policy in urban Indonesia.